Pengaruh Brand Image dan Gaya Hidup Terhadap Keputusan Pembelian Baju Thrift di CFD Telanai Kota Jamb - Dionna Andini Putri; Novi Mubyarto; Firman Syah Noor (JOURNAL OF SHARIA ECONOMICS, 2025)
The growth of the thrift clothing business in Indonesia has increasedsignificantly along with the rising trend of sustainable fashion andchanges in consumer lifestyles. Consumers' purchasing decisions forthrift clothing are influenced not only by economic considerations butalso by brand image and lifestyle, particularly among youngconsumers. This study aims to examine the influence of brand imageand lifestyle on purchasing decisions for thrift clothing at CFDTelanai, Jambi City, both partially and simultaneously. This researchemployed a quantitative approach with an explanatory researchdesign. A total of 70 respondents were selected using a purposivesampling technique. Data were collected through questionnaires andanalyzed using multiple linear regression with IBM SPSS Statistics.The findings indicate that brand image has a positive and significanteffect on purchasing decisions. Likewise, lifestyle also has a positiveand significant effect on purchasing decisions. Simultaneously, brandmage and lifestyle significantly influence consumers' purchasingdecisions for thrift clothing at CFD Telanai, Jambi City. These findingssupport the Theory of Planned Behavior, which explains thatndividual attitudes and characteristics influence purchasing behavior.This study contributes to the literature on consumer behavior andprovides practical implications for thrift business owners in developingmore effective marketing strategies